My brain knows numbers! - an ERP study of preschoolers’ numerical knowledge - Ben-Shalom, Tamar; Berger, Andrea; Henik, Avishai (Frontiers in Psychology, 2013)
This study investigated brain activity in numerical processing at early stages of development. Brain activity of preschoolers was obtained while they performed a numerical Stroop task. Participants were asked to decide which of two digits was numerically or physically larger. Behavioral distance and size congruity effects were found. However, a reverse facilitation was observed, where responses to neutral trials were faster than to congruent ones. Brain activity showed that 6-year-old children activate frontal areas related to conflict, as well as parietal areas related to mature numerical processing. Moreover, there was a difference between the timing of the interference compared to the facilitation components in the size congruity effect. In parietal areas, facilitation was significant in an early time window and interference was significant at a later time window. This is consistent with the idea that facilitation and interference are separate processes. Our findings indicate that children as young as 5-6 years old can automatically process the numerical meaning of numerals. In addition, brain activity during the numerical Stroop task showed that at this age, children use both frontal and parietal areas in order to process irrelevant numerical information.